(untitled) (Zdravstveni glasnik, 2024)
Introduction: There are many factors that can have an impact on the injury of soccer players. It is very difficult to predict all factors, so turning to prevention, collecting data on injury patterns, and designing new strategies for injury prevention among soccer players is extremely important. Objective: To determine the condition of lower limb injuries in football players of the Premier League of Bosnia and Herzegovina Methods: Professional soccer players competing in the Premier League of Bosnia and Herzegovina participated in a retrospective study. For this study, each soccer player filled out a questionnaire that was not standardized but was designed for the purposes of this research. Complaints about injuries during 2019 were requested, as well as insight into types of injuries, methods of treatment, use of orthoses, bandages, and the like. Results: Out of a total of 129 subjects, 57.4 % had injuries, of which 50 had only one injury. Most respondents were injured during training (64.9 %), on normal surfaces (82.4 %). In 44.6 % of respondents, it was a non-contact, new injury, more often on the non-dominant leg, the most frequently injured were muscles. 26 of them had an operation, and the recovery of the majority lasted up to 40 days. Conclusion: Exposure to various risk factors resulted in lower limb injuries in more than half of the respondents.